Edukasi Teoretis Kehalalan Pangan dan Manajemen Higienitas Sanitasi Daging Bersama Komunitas Juleha Lokal di Universitas Bima Sakapenta - Muh. Sahidun; Mochamad Sya’ Bani; Ulul Absor; Sri Rahayu; Apriyani Apriyani (Asosiasi Riset Ilmu Pendidikan Indonesia, 2026)
The urgency of quality assurance in animal-derived food demands the acceleration of traditional slaughterers' competence toward modern standardization. This community service program aims to improve cognitive understanding regarding occupational safety and post-slaughter hygiene sanitation among 80 Halal Slaughterers (Juleha). Theoretical educational interventions were carried out in classrooms at Bima Sakapenta University on Saturday during the even semester, while operational activities were located outside the campus. The community development method implemented participatory planning with action research strategies through four systematic stages, measured using descriptive statistical comparative assessment. Program results recorded a surge in the group's average score from an initial pre-test score of 75.00 to 83.31 in the final post-test achievement. In conclusion, this scientific reinforcement contributes significantly to accelerating the transformation of partners' working paradigms to be regulation-compliant. The practical benefit is an increased independent skill in mitigating occupational hazards and carcass contamination, while the theoretical benefit enriches the literature on faith-based food science dissemination models.